2018
DOI: 10.9753/icce.v36.papers.75
|View full text |Cite
|
Sign up to set email alerts
|

Stability Comparison of 9 Modern Placed Block Revetment Types for Slope Protections

Abstract: Placed block revetments are constructed to withstand the wave forces on dikes, especially in regions where rip rap is not locally available, such as the Netherlands. The blocks are placed adjacent to each other on a filter layer to form a relatively closed and smooth surface, which is easy to walk on. Large-scale test in the Delta Flume of Deltares have been carried out to compare the stability of nine types of block revetments, presently on the market in the Netherlands (Klein Breteler, 2016). All tests have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Applying the step-by-step plan reduced the need for reinforcement on many projects, and at some locations, reinforcement proved to no longer be necessary. Various studies have also been carried out on piping [38,39] and the deterioration of revetments [40,41] (see also Figure 7b), making safety factors explicit, so that the need for reinforcement can be determined more accurately. Furthering the knowledge uptake will limit the scope of the programme Water 2022, 14, x FOR PEER REVIEW 14 of 19 looked at the opportunities for, and impediments to, legislation and regulations.…”
Section: Monitoring Knowledge and Innovationmentioning
confidence: 99%
“…Applying the step-by-step plan reduced the need for reinforcement on many projects, and at some locations, reinforcement proved to no longer be necessary. Various studies have also been carried out on piping [38,39] and the deterioration of revetments [40,41] (see also Figure 7b), making safety factors explicit, so that the need for reinforcement can be determined more accurately. Furthering the knowledge uptake will limit the scope of the programme Water 2022, 14, x FOR PEER REVIEW 14 of 19 looked at the opportunities for, and impediments to, legislation and regulations.…”
Section: Monitoring Knowledge and Innovationmentioning
confidence: 99%
“…Dike cover erosion due to wave loads by overtopping waves could eventually lead to dike breaching, which can result in severe losses of properties and lives. Experiments [5][6][7][8][9][10] and numerical models [11,12] have shown that erosion on dikes is mainly caused by wave loads, such as pressure, normal stress, shear stress and flow velocities. Therefore, accurate estimations of these wave loads are important for dike designs and safety assessments.…”
Section: Introductionmentioning
confidence: 99%